Building a Foundation for Digital Animation - Castillo, Paulynne (Animo Repository, 2017)
An analysis of the Philippine digital animation sub-sector reveals that the key areas on which resources should be focused to move up the industry’s value chain are: 1) recruiting, developing, and retaining talent; 2) financing the cultivation of original content; and 3) expanding and improving the country’s information communication technology (ICT) infrastructure.